بناء معيار لقياس التعبير الشفوي لدى تلامذة المرحلة الابتدائية (Journal Of Educational and Psychological Researches, 2016)
Given the importance of basic education (primary) being longer pillar in the construction of the individual's personality, as well as the importance of language and its role in the learning of students and development of cognitive, emotional and self-dynamic; therefore current research focuses on the study of building a standard oral expression can researchers and teachers alike measurement of oral expression among students, researcher has used to achieve this goal descriptive approach, it included standard on (10) paragraphs evenly distributed on the (5) key areas, and given (4) progressive alternatives according to the quality of the performance of the student and reached the highest score (30) and the lowest score (0).Among the recommendations that came out of research: enrich the subjects of expression and conversation in the primary stage Koran verses and sayings and poetry and that develop in students the high values ​​and imagination. Can the Arabic language teachers at the elementary level to take the standard oral expression tool to measure the level of the students in this article.And research proposals: conduct a study on the relationship of oral expression with other variables, such as attention and memory. conducting a similar study for the construction of a standard for the oral expression of intermediate cheerful students.